Orthogonal matching pursuit with DCD iterations. Issue 4 (1st February 2013) - Zakharov, Y.V.; Nascimento, V.
Abstract : Greedy algorithms are computationally efficient optimisation techniques for solving sparse recovery problems. Matching pursuit (MP) and orthogonal MP (OMP) are popular greedy algorithms; MP possesses the lowest complexity whereas OMP provides better performance. In this reported work, OMP is modified using dichotomous coordinate descent (DCD) iterations and an algorithm is arrived at that has performance close to that of OMP and complexity even lower than that of MP.